2015
DOI: 10.2196/jmir.3965
|View full text |Cite
|
Sign up to set email alerts
|

Successful Organizational Strategies to Sustain Use of A-CHESS: A Mobile Intervention for Individuals With Alcohol Use Disorders

Abstract: BackgroundMobile health (mHealth) services are growing in importance in health care research with the advancement of wireless networks, tablets, and mobile phone technologies. These technologies offer a wide range of applications that cover the spectrum of health care delivery. Although preliminary experiments in mHealth demonstrate promising results, more robust real-world evidence is needed for widespread adoption and sustainment of these technologies.ObjectiveOur aim was to identify the problems/challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…Outside of schizophrenia research, one recent study examined how a mobile app intervention for alcoholism could scale beyond a single clinical study 36 to regional clinics. The study noted that the app faced numerous barriers in scaling up; with only 15% of clinics still using it at two years 37 . In part, the potential of smartphone interventions to address population-level unmet needs, and to provide remote support to those who cannot physically access clinical services, has driven the interest in using this technology for schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Outside of schizophrenia research, one recent study examined how a mobile app intervention for alcoholism could scale beyond a single clinical study 36 to regional clinics. The study noted that the app faced numerous barriers in scaling up; with only 15% of clinics still using it at two years 37 . In part, the potential of smartphone interventions to address population-level unmet needs, and to provide remote support to those who cannot physically access clinical services, has driven the interest in using this technology for schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…There was only one study focusing explicitly on prerequisites for a successful implementation of digital interventions. In a study on the implementation of A-CHESS, Ford (2015) found that the following factors were important for a successful and sustained implementation of the intervention: strong leadership support, a staff that is passionate about the intervention, utilizing user feedback to re-engage users who had dropped out, including the intervention in meetings with staff and users, developing internal guidelines for utilizing the intervention, and developing sustainable strategies for financing the intervention.…”
Section: Methodsmentioning
confidence: 99%
“…The simple interventions seemed relatively easy to develop and implement, especially those using standard text messaging and smartphone applications. Complex interventions seemed also easy to implement, but the study by Ford [62] showed that there are many organizational prerequisites to achieving a sustainable implementation of such interventions over time. In addition to questions about feasible technical solutions, it is important to determine whether the organizational prerequisites are in place to sustain the implementation over time before implementing a digital intervention.…”
Section: Feasibility Strengths and Weaknessesmentioning
confidence: 99%
“…Additional unique possibilities by applying telemedicine facilitates monitoring using up-to-date mobile technology [24]. Focusing on monitoring and preventing the relapse of alcohol addicts using smartphones, Gustafson et al [25] proved the effectiveness of smartphone monitoring. Specialized and personalized intervention is possible only based on individually monitored specific data and evidence.…”
Section: Total System Architecturementioning
confidence: 99%